Impacts of brick kiln emission on agricultural soil around brick kiln areas (Nepal Journal of Environmental Science, 2021)
The study attempted to assess the impacts of the brick kilns emissions on the farm soil in and around the kiln areas. A total of 72 representative farm soil samples were collected from 12 selected brick kiln clusters in Rajshahi and Gazipur Districts of Bangladesh, covering two years (September 2015 to August 2017). The collected samples were analyzed using standard methods. The pH and organic matter content in the farm soil samples were found to be very low. The farm soil parameters such as pH, organic matter, and soil texture were found in critical conditions. Among all of the heavy metals, only Cr exceeded the permissible standard of some soil samples. The concentration of Cr ion varied from 9.50 to 52.77 and 16.54 to 70.13 ppm in Rajshahi and Gazipur Districts, respectively indicated the chance of metal contamination in plants. The study results showed that the values of contamination factor (Cif) and ecological risk factor (Eir) in the selected farm soil of Rajshahi and Gazipur Districts existed in the order of Cd > As > Cr > Pb > Zn and Cd > As > Pb > Cr > Zn, respectively. The study results also showed that the pollution load index and risk index values were lower than 1 and 150, respectively, at all sampling locations indicating lower pollution and risk from heavy metals in the areas. The study observed that continuous brick production over the periods degraded topsoil fertility and reduced agricultural productivity.